2016
DOI: 10.3390/su8060558
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Modular Prefabricated Architecture: Case Study-Based Review and Future Pathways

Abstract: Even though tightened building energy efficiency standards are implemented periodically in many countries, existing buildings continually consume a momentous quota of the total primary energy. Energy efficiency solutions range from material components to bulk systems. A technique of building construction, referred to as prefabricated architecture (prefab), is increasing in reputation. Prefab encompasses the offsite fabrication of building components to a greater degree of finish as bulk building structures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 47 publications
1
72
0
Order By: Relevance
“…For the construction 4.0 concepts that support the establishment of a smart construction site, table 2 showed that the respondents are very ready to adopt prefabrication/modularization and the use of radio frequency identification (RFID) for construction activities during the delivery of houses. Their readiness to use prefabrication and RFID can be related to the already established benefit of adopting prefabrication in other developed countries as shown by authors such as [45], [46]. Likewise, the use of RFID has been prescribed by authors such as Sardroud [43], Costin and Telzer [44] they discover that it allows the automation of construction process by allowing effective tracking of equipment and tools, theft prevention and inventory management.…”
Section: Readiness To Adopt Construction 40mentioning
confidence: 99%
“…For the construction 4.0 concepts that support the establishment of a smart construction site, table 2 showed that the respondents are very ready to adopt prefabrication/modularization and the use of radio frequency identification (RFID) for construction activities during the delivery of houses. Their readiness to use prefabrication and RFID can be related to the already established benefit of adopting prefabrication in other developed countries as shown by authors such as [45], [46]. Likewise, the use of RFID has been prescribed by authors such as Sardroud [43], Costin and Telzer [44] they discover that it allows the automation of construction process by allowing effective tracking of equipment and tools, theft prevention and inventory management.…”
Section: Readiness To Adopt Construction 40mentioning
confidence: 99%
“…However, most of the previous studies on construction industrialization concentrated on the technical aspects of the system, energy analysis, energy efficiency and Building Information Modeling [5,6], with only a limited number of studies being conducted on the regional development level of construction industrialization. Wang and Ji analyzed various factors they believed were affecting development of construction industrialization in China, before building a system that incorporated these influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…An automated prefabrication of singular timber elements has been demonstrated on various research studies and projects in the last decades (Sass 2007;Beyer 1991;Scheurer 2011). The degree of prefabrication describes the size and complexity of prefabricated components, which is directly related to the amount of on-site construction labor, material use, construction quality, and, therefore, sustainability performance (Boafo et al 2016). Even today, CNC technologies are used predominantly for subtractive processes in the industry (Popovic et al 2016), which can also be noted in the available manufacturing techniques of current timber production lines (Hans Hundegger 2016).…”
Section: Prefabricationmentioning
confidence: 99%